(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Obstructive sleep apnea (OSA) is increasingly recognized as a major cardiovascular comorbidity linked to hypertension, arrhythmia, coronary artery disease, and heart failure, particularly heart failure with preserved ejection fraction (HFpEF). Repetitive nocturnal hypoxemia, sympathetic activation, and adverse cardiac loading may accelerate structural and functional myocardial abnormalities. This study evaluated the burden of OSA-related cardiovascular abnormalities among adults admitted with cardiovascular disease and explored its relation to echocardiographic markers of heart failure. Methods: This hospital-based observational study included 100 adults evaluated at Aster Prime Hospital between 2020 and 2023. The cohort comprised 50 men and 50 women. Patients underwent symptom-based clinical assessment, STOP-BANG screening, polysomnography with apnea-hypopnea index (AHI) measurement, and transthoracic echocardiography including left ventricular ejection fraction (LVEF), left atrial (LA) size, pulmonary artery pressure, tricuspid regurgitation (TR), tissue Doppler E/e′, left ventricular hypertrophy (LVH), global longitudinal strain (GLS), and right ventricular systolic function by tricuspid annular plane systolic excursion (TAPSE). Analyses were descriptive. Results: Seventy percent of participants had STOP-BANG scores ≥5 and an equivalent proportion had AHI >5/h, indicating a high burden of OSA. Abnormal relaxation on echocardiography was present in 85% of the cohort, prolonged deceleration time (>240 ms) in 85%, and abnormal E/e′ in 75%, supporting a dominant diastolic dysfunction phenotype. LVH was identified in 60%, impaired GLS in 40%, pulmonary hypertension in 65%, and abnormal TAPSE in 35%. Preserved LVEF (>50%) was present in 70%, while 55% had an HFA-PEFF/HFpEF-related score >5, suggesting probable HFpEF. OSA severity showed a clinically parallel relationship with worsening diastolic indices, atrial enlargement, atrial fibrillation, pulmonary hypertension, and treatment escalation from lifestyle intervention to CPAP or bilevel positive airway pressure. Conclusion: OSA was highly prevalent in this cardiovascular cohort and closely accompanied by diastolic dysfunction, pulmonary vascular burden, and a predominant HFpEF phenotype. Early recognition of sleep-disordered breathing in heart failure care pathways may improve risk stratification and support more integrated treatment.